ON EXPERIENCE OF THE INTEGRATION OF THE GOOGLE APPS FOR EDUCATION CLOUD SERVICES WITH THE EXISTING INFORMATIONAL INFRASTRUCTURE OF THE MEDICAL UNIVERSITY - A. V. Semenets; V. Yu. Kovalok; S. B. Chekanov (Medična Informatika ta Inženerìâ, 2015)
Some aspects of informatization of the medical ed ucation field are considered. The problem of providing the interoperability between cloud services and information systems that can exist in the medical university is determined. The approach of the integration of the Google Apps for Education cloud services with the existing information systems based on the Google Apps For Developers features is propose d. The example of the integration solution in Ternopil State Medical University by I. Ya. Horbachevsky which is based on the "SysAdminka" information system development is shown. Practical recipes of the application of the School Directory Sync util as the "SysAdminka" information system component are offered.